IMPLEMENTATION OF THE TOPSIS METHOD IN DETERMINING THE BEST PHYSICS LEARNING MEDIA AID WITH ROC WEIGHTING - Mesran; Soeb Aripin; Tesa Aurelia Siregar (Journal of Islamic, Social, Economics and Development, 2023)
In the era of highly developed, it is very influential in various sectors, including one that is experiencing technological changes that are increasingly sophisticated, so that it can make it easier for students to carry out the learning process using media that has been widely used. physics learning media aids often occur several problems because the learning media is expensive and lacks features in the application of learning media and the explanation is not understood by students can make it difficult for students to use and choose suitable media tools in helping physical learning. In the best physics learning media tools, there are five criteria including user capacity, visual interaction, friendly features, application features and internet data usage. So, in this research, the assistant system was ordered to solve the problems that occurred in the research. The system referred to as a problem solving tool is a Decision Support System (DSS). Based on these problems, a decision support system is needed as a problem-solving technique and is assisted by methods that can produce accurate final scores. The method is the TOPSIS method and the ROC weighting which is very helpful in generating weights from alternative data and criteria so as to get the final results obtained from Alternative M3, the name of the application is Ruang Guru with a value of 0.9998